Activitas Nervosa Superior The Journal for Neurocognitive Research - Bob, Petr.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Activitas Nervosa Superior is an international peer-reviewed journal that publishes original research of basic, clinical and theoretical findings of brain and mental processes, as well as diseases of the nervous system within the spectrum of natural to mind sciences. The fields of neuroscience, psychology, psychiatry, psycho- neuroendocrinology and neuroimmunology, computational and systems modeling, and neurophysics and related molecular and cellular processes are all covered. The journal welcomes scholarly reviews. Articles focused on basic conceptual and philosophical problems of neuroscience and psychology are also within the scope of the journal, as are editorials, case studies, and short communications. The main aim of the journal is to facilitate an understanding of the fundamental mechanisms of neural and cognitive processes and the transfer of basic information to clinical applications.
Keywords: Psychology; Neuropsychology; Experiential research; Cognitive psychology; Psychology, Experimental; Cognitive Psychology; Neuropsychology; Psychology Research; Psychology, general; Experimental Psychology